Mediación Didáctica para la Enseñanza de la Historia del Período Liberal del siglo XIX en Colombia a partir del Graffiti como Recurso Didáctico en Grado Noveno de Básica Secundaria (2023)
This research monograph stems from the idea of how to teach the liberal period in Colombia during the 19th century. To this end, a didactic mediation is proposed as a starting point to allow the development of the research monograph in line with the proposal of Antonio Nariño University in this modality, using graffiti as a teaching resource at La Portada Academic Institute. Additionally, this undergraduate project aims to propose an innovative action that takes into account actions to enhance history teaching, such as the artistic expression of graffiti.